A polymer-based composite thermal interface material and preparation method thereof

By preparing the metal-carbon nano-nano-tube nano-nuclear shell structure, the stable liquid metal enhanced polymer base composite material flexible thermal interface material of the existing polymer base thermal interface material has been solved, and the high thermal conductivity coefficient and the high thermal conductivity coefficient and The heat interface material with good heat dissipation performance is suitable for thermal management of high -power electronic devices.

CN118459912BActive Publication Date: 2025-01-24SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410613768.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-17
Publication Date
2025-01-24
Estimated Expiration
2044-05-17

AI Technical Summary

Technical Problem

The existing polymer-based thermal interface materials have low thermal conductivity and cannot effectively cope with the thermal management needs in high-power electronic devices, resulting in reduced performance and shortened lifetime.

Method used

By preparing a liquid metal-reinforced polymer-based composite flexible thermal interface material with a stable network of metallic ruthenium-carbon nanotube nanocore-shell structures, its thermal conductivity and heat dissipation performance are improved.

Benefits of technology

The thermal conductivity of the polymer-based thermal interface material is significantly increased to 24.65W·m-1·K-1, which improves the heat dissipation performance and flexibility of electronic devices and is suitable for thermal management of high-power electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118459912B_ABST
    Figure CN118459912B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of thermal management of electronic devices, and relates to a polymer-based composite thermal interface material and a preparation method thereof. The polymer-based composite thermal interface material prepared by the present invention is a liquid metal-reinforced polymer-based composite flexible thermal interface material with a metal ruthenium-carbon nanotube nanocore-shell structure network stability, which is formed by mixing and solidifying polyvinyl alcohol resin, metal ruthenium-carbon nanotube nanocore-shell structure powder, and liquid metal gallium-indium alloy. The diameter of the metal ruthenium-carbon nanotube nanocore-shell structure is about 20 to 200 nm, and it has an extremely high aspect ratio, which can effectively form a three-dimensional grid structure. The radial thermal conductivity of the polymer-based composite thermal interface material is as high as 24.65 W·m ‑1 ·K ‑1 , thermal conductivity in vertical direction 7.53W·m ‑1 ·K ‑1 , has good heat dissipation performance and flexibility, can be prepared in batches, and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electronic device thermal management, and in particular to a polymer-based composite material thermal interface material and a preparation method thereof. Background Art

[0002] With the rapid development of integrated circuit technology, advanced process technology has made new breakthroughs. While the integration level has been greatly improved, the chip speed and computing power have also been continuously improved. The heat flux density per unit area of ​​the chip has increased sharply. The resulting high power consumption has led to increasingly serious chip overheating problems, which may even develop into a key problem that limits the continued validity of Moore's Law. At present, the heat flux density of the chip during operation has exceeded 100W·cm -2 If such a high-density heat flow cannot be discharged in time, the chip operating temperature will be too high, which will lead to a series of problems such as performance degradation, shortened life, and even failure. Therefore, effective thermal management is particularly important in ensuring the normal operation of the chip. In addition, effective heat dissipation is also crucial for other electronic devices or systems, such as batteries, lasers, high-power LEDs, etc.

[0003] Chip heat dissipation is mainly achieved by heat conduction. However, the surface roughness between the chip and the heat sink leads to the existence of air gaps. Since the thermal conductivity of air is extremely low (~0.024W·m -1 ·K -1 ), which will seriously hinder the heat conduction from the chip to the heat sink, and then cause a large amount of heat to accumulate inside the electronic device, resulting in performance degradation and shortened life. In order to solve this key problem, it is necessary to introduce a layer of high thermal conductivity material between the chip and the heat sink to fill the gap to ensure that the heat can be effectively transferred to the heat sink. This layer of material is called thermal interface material.

[0004] Common thermal interface materials are mainly divided into two categories: metal-based and polymer-based. Metal-based thermal interface materials are usually used as solder to weld the heat source and heat sink together. Common materials include liquid metal indium, tin and other pure metals and their alloys. The thermal conductivity of metal-based thermal interface materials is very high, which can reach 30~80W·m -1 ·K -1 However, due to problems such as mismatched thermal expansion coefficients, stress and cracks are easily generated, which in turn lead to device failure. Polymer-based thermal interface materials are the most common and widely used thermal interface materials. They are usually made of polymer materials such as silicone oil, silicone grease, rubber and epoxy resin as the base, and are prepared by adding high thermal conductivity fillers such as copper, silver, zinc oxide and carbon materials to the base. At present, the thermal conductivity of polymer-based thermal interface materials is relatively low, usually about 1 to 5 W·m -1 ·K -1However, due to its good fluidity, flexibility, and wide applicability, it is the most popular thermal interface material in commercial applications and academic research. Further improving the thermal conductivity of polymer-based thermal interface materials is the key to meeting the increasing demand for thermal management, and is of great significance for ensuring the stability of electronic device system performance and promoting the development of high-power electronic device systems. Summary of the invention

[0005] The purpose of the present invention is to provide a polymer-based composite thermal interface material and a preparation method thereof to solve the problems existing in the above-mentioned prior art. Specifically, the present invention improves the thermal conductivity and heat dissipation performance of the polymer-based thermal interface material by preparing a liquid metal reinforced polymer-based composite flexible thermal interface material with a stable network of metal ruthenium-carbon nanotube nanocore-shell structure.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing a polymer-based composite thermal interface material, the steps comprising:

[0008] By alternately introducing cyclopentadienylruthenium gas and oxygen to grow a metal ruthenium atomic deposition layer on the three-dimensional network structure of carbon nanotubes, a metal ruthenium-carbon nanotube nano core-shell structure membrane is obtained;

[0009] The metal ruthenium-carbon nanotube nano core-shell structure film is ground to obtain the metal ruthenium-carbon nanotube nano core-shell structure powder;

[0010] Metal ruthenium-carbon nanotube nano core-shell structure powder is added with ethanol to prepare metal ruthenium-carbon nanotube ethanol dispersion suspension;

[0011] The metal ruthenium-carbon nanotube nano core-shell structure powder, the liquid gallium-indium alloy and the metal ruthenium-carbon nanotube ethanol dispersion suspension are mixed and ground to obtain a paste;

[0012] A polyvinyl alcohol resin aqueous solution is added to the paste, mixed evenly, and then cured to obtain the polymer-based composite material thermal interface material.

[0013] Furthermore, the steps of preparing the three-dimensional carbon nanotube network structure include:

[0014] Dispersing carbon nanotubes and surfactant in a solvent to prepare a carbon nanotube dispersion with a concentration of 5 wt %;

[0015] coating the carbon nanotubes in the carbon nanotube dispersion on a silicon substrate, and drying to remove the solvent to obtain a carbon nanotube film structure;

[0016] The carbon nanotube film structure is subjected to heating treatment to obtain the carbon nanotube three-dimensional network structure.

[0017] Preferably, the mass ratio of the carbon nanotubes to the surfactant is 5 to 10:1.

[0018] Preferably, the solvent is water or an organic solvent; the surfactant is sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone or sodium deoxycholate.

[0019] More preferably, the organic solvent comprises ethanol or isopropanol.

[0020] Preferably, the method of coating the carbon nanotubes in the carbon nanotube dispersion on the silicon substrate comprises drip coating, spray coating or dipping.

[0021] Preferably, the heat treatment is: heating at 300-400° C. for 1-3 hours in air, and then heating at 600-1000° C. for 3-5 hours in an inert atmosphere to remove the surfactant.

[0022] More preferably, the inert atmosphere is a nitrogen atmosphere or a helium atmosphere.

[0023] Furthermore, the particle size of the metal ruthenium-carbon nanotube nano core-shell structure powder is not greater than 10 μm.

[0024] Furthermore, the metal ruthenium-carbon nanotube ethanol dispersion suspension is prepared by dispersing the metal ruthenium-carbon nanotube nano core-shell structure powder in ethanol at a mass / volume ratio of 1 g:10 mL.

[0025] Furthermore, when preparing the paste, the mass / volume ratio of the metal ruthenium-carbon nanotube nano core-shell structure powder, the liquid gallium-indium alloy and the metal ruthenium-carbon nanotube ethanol dispersion suspension is 1g:10g:10mL.

[0026] Furthermore, the mass concentration of the polyvinyl alcohol resin aqueous solution is 10%.

[0027] Furthermore, the mass / volume ratio of the liquid gallium-indium alloy and the polyvinyl alcohol aqueous solution in the paste is 10 g:20 mL.

[0028] Furthermore, the curing temperature is 45 to 55° C. and the curing time is 2 to 5 hours.

[0029] Furthermore, the metal ruthenium atomic deposition layer can be prepared by an atomic layer deposition apparatus.

[0030] The second technical solution of the present invention is to provide a polymer-based composite thermal interface material prepared by the above method.

[0031] The third technical solution of the present invention is to provide an application of the above-mentioned polymer-based composite thermal interface material in improving the stability of electronic device systems.

[0032] The present invention discloses the following technical effects:

[0033] The polymer-based composite thermal interface material prepared by the present invention is a liquid metal-reinforced polymer-based composite flexible thermal interface material with a metal ruthenium-carbon nanotube nanocore-shell structure network stability, which is prepared by mixing and curing polyvinyl alcohol resin, metal ruthenium-carbon nanotube nanocore-shell structure powder, and liquid metal gallium-indium alloy. The diameter of the metal ruthenium-carbon nanotube nanocore-shell structure powder is about 20 to 200 nm, and it has an extremely high aspect ratio, and can effectively form a three-dimensional grid structure.

[0034] Since ruthenium and carbon nanotubes are both highly thermally conductive materials, the three-dimensional grid structure provides a good thermal conductive framework for polymer-based composite materials. In addition, the metal ruthenium and the liquid metal gallium indium alloy form an electronic heat conduction path, which can effectively reduce the interface Umklapp scattering of electrons and phonons, further improving the thermal conductivity of polymer-based composite materials.

[0035] Metallic ruthenium and gallium in the liquid metal gallium-indium alloy can form the intermetallic compound RuGa3, and bind the liquid metal gallium-indium alloy through a three-dimensional nano-network structure, greatly improving the filling rate of the liquid metal gallium-indium alloy in the polymer-based composite material, and significantly improving the problem of easy flow and overflow of liquid metal when the polymer-based composite material is subjected to external pressure.

[0036] The radial thermal conductivity of the liquid metal reinforced polymer-based composite material flexible thermal interface material with a stable network of metal ruthenium-carbon nanotube nanocore-shell structure prepared by the present invention is as high as 24.65 W·m -1 ·K -1 , thermal conductivity in vertical direction 7.53W·m -1 ·K -1 , has good heat dissipation performance and flexibility, can be prepared in batches, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 The microscopic morphology and synthesis process diagram of the metal ruthenium-carbon nanotube nano core-shell structure film prepared in Example 1;

[0039] Figure 2The actual picture of the polymer-based composite thermal interface material prepared in Example 1 and the actual picture of the material bent 180°;

[0040] Figure 3 This is a cross-sectional view of the polymer-based composite thermal interface material prepared in Example 1;

[0041] Figure 4 These are fiber morphology images of the polymer-based composite thermal interface material prepared in Example 1, where (a) is a 2D laser image, (b) is a 2D color image, (c) is a 3D color image, and (d) is a height image; all were taken using a 3D laser confocal microscope.

[0042] Figure 5 This is a physical picture of the composite material prepared in Comparative Example 2;

[0043] Figure 6 It is a schematic structural diagram of a polymer-based composite thermal interface material prepared in an embodiment of the present invention. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] In a specific embodiment of the present invention, the diameter of a single metal ruthenium-carbon nanotube nanocore-shell structure in the prepared metal ruthenium-carbon nanotube nanocore-shell structure is 20-200 nm, and the aspect ratio is 5-500.

[0050] The liquid gallium-indium alloy described in the embodiment of the present invention has a ratio of Ga:In=75:25 and a melting point of 16°C.

[0051] Example 1

[0052] The preparation steps of polymer-based composite thermal interface materials are as follows:

[0053] S1, mixing 5 g of carbon nanotube powder with 1 g of a surfactant, sodium dodecyl sulfate, and dispersing them in water by ultrasonication to prepare a carbon nanotube dispersion with a concentration of 5 wt %;

[0054] S2, applying the dispersed liquid droplets onto a silicon substrate, forming a carbon nanotube film structure after drying, placing the carbon nanotube film structure on a heating plate, heating it at 400° C. in air for 1 hour, and then placing it in a tubular furnace and heating it at 600° C. in a nitrogen atmosphere for 3 to 5 hours until the surfactant is completely removed, thereby obtaining a three-dimensional carbon nanotube network structure;

[0055] S3, placing the carbon nanotube three-dimensional network structure in the reaction chamber of the atomic layer deposition instrument at 330°C and 10 -5 Pa pressure, introducing cyclopentadienylruthenium gas, the residence time of the cyclopentadienylruthenium gas in the cavity is more than 1 s, so that the cyclopentadienylruthenium is adsorbed on the surface of the three-dimensional network structure of the carbon nanotube and the internal pores, and then introducing nitrogen to purge out the residual cyclopentadienylruthenium gas, and then introducing oxygen, the oxygen reacts with the cyclopentadienylruthenium molecules adsorbed on the surface of the three-dimensional network structure of the carbon nanotube and the surface of the internal pores, and epitaxially grows to form a metal ruthenium film, and then introducing nitrogen to purge out the residual oxygen, and repeating this step 300 times to obtain a metal ruthenium-carbon nanotube nano core-shell structure film;

[0056] S4, grinding the metal ruthenium-carbon nanotube nano core-shell structure film to obtain metal ruthenium-carbon nanotube nano core-shell structure powder;

[0057] S5, dispersing the metal ruthenium-carbon nanotube nanocore-shell structure powder in ethanol to obtain a metal ruthenium-carbon nanotube ethanol dispersion suspension, wherein the mass / volume ratio of the metal ruthenium-carbon nanotube nanocore-shell structure powder to ethanol is 1 g:10 mL;

[0058] S6, mixing and grinding 1 g of metal ruthenium-carbon nanotube nano core-shell structure powder, 10 g of liquid gallium-indium alloy and 10 mL of metal ruthenium-carbon nanotube ethanol dispersion suspension to obtain a paste;

[0059] S7. Stir and mix the paste obtained in step S6 with 20 mL of polyvinyl alcohol resin aqueous solution (concentration of 10%) to evenly mix, and then cure it at 55°C (2h) to obtain a liquid metal reinforced polymer-based composite material with a stable network of ruthenium-carbon nanotube nanocore-shell structure, which is a polymer-based composite material thermal interface material.

[0060] Comparative Example 1

[0061] Compared with Example 1, the only difference is that no liquid gallium-indium alloy is added.

[0062] If liquid gallium-indium alloy is not added, the thermal conductivity of the polymer-based composite material formed by the metal ruthenium-carbon nanotube nanocore-shell structure and the polyvinyl alcohol resin is only about 0.5W / mK, which is significantly lower than the liquid metal reinforced polymer-based composite material with a stable network of metal ruthenium-carbon nanotube nanocore-shell structure in the present invention.

[0063] Comparative Example 2

[0064] Compared with Example 1, the only difference is that no metal ruthenium-carbon nanotube nano core-shell structure powder is used, that is, the composite material is obtained by mixing and solidifying only polyvinyl alcohol resin, carbon nanotube powder and liquid metal gallium indium alloy.

[0065] Test example

[0066] Figure 1 Schematic diagram of the microscopic morphology and synthesis process of the metal ruthenium-carbon nanotube nano core-shell structure film prepared in Example 1.

[0067] Figure 2 The actual picture of the polymer-based composite thermal interface material prepared in Example 1 and the actual picture of the material being bent 180° show that the polymer-based composite thermal interface material prepared in the present invention has excellent flexibility and can be bent repeatedly 180°.

[0068] Figure 3 This is a cross-sectional view of the polymer-based composite thermal interface material prepared in Example 1, taken by a 3D confocal microscope. Figure 3 It can be seen that the thickness of the prepared polymer-based composite thermal interface material is uniform, and the liquid metal with a stable network of metal ruthenium-carbon nanotube nanocore-shell structure is evenly distributed in the polyvinyl alcohol resin without obvious agglomeration and overflow.

[0069] Figure 4The fiber morphology of the polymer-based composite thermal interface material prepared in Example 1, where (a) is a 2D laser image, (b) is a 2D color image, (c) is a 3D color image, and (d) is a height image, all taken by a 3D laser confocal microscope. Figure 4 It can be seen that the liquid metal with a stable network of ruthenium-carbon nanotube nanocore-shell structure is dispersed into a size below 100 μm and evenly distributed in the polyvinyl alcohol resin. The thickness error of the prepared polymer-based composite thermal interface material can be controlled below 50 μm.

[0070] Figure 5 This is a physical picture of the composite material prepared in Comparative Example 2. Figure 5 It can be seen that the liquid gallium-indium alloy agglomerates in large quantities and cannot form a uniform composite material.

[0071] Figure 6 It is a schematic structural diagram of a polymer-based composite thermal interface material prepared in an embodiment of the present invention.

[0072] The thermal conductivity performance of the polymer-based composite thermal interface material prepared in Example 1 was evaluated by laser flash spectroscopy and differential scanning calorimetry.

[0073] The thermal diffusivity, specific heat and thermal conductivity of the polymer-based composite thermal interface material prepared in Example 1 at 25°C, 50°C and 80°C are shown in Table 1 (the thickness of the test sample is 0.989 mm and the density is 1.303 g / cm 3 ).

[0074] Table 1

[0075]

[0076] It can be seen from the data in Table 1 that the thermal conductivity of the prepared polymer-based composite thermal interface material does not decrease under the atmospheric conditions of 50°C and 80°C.

[0077] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a polymer-based composite thermal interface material, characterized in that the steps include: By alternately introducing cyclopentadienylruthenium gas and oxygen to grow a metal ruthenium atomic deposition layer on the three-dimensional network structure of carbon nanotubes, a metal ruthenium-carbon nanotube nano core-shell structure membrane is obtained; The metal ruthenium-carbon nanotube nano core-shell structure film is ground to obtain the metal ruthenium-carbon nanotube nano core-shell structure powder; Metal ruthenium-carbon nanotube nano core-shell structure powder is added with ethanol to prepare metal ruthenium-carbon nanotube ethanol dispersion suspension; The metal ruthenium-carbon nanotube nano core-shell structure powder, the liquid gallium-indium alloy and the metal ruthenium-carbon nanotube ethanol dispersion suspension are mixed and ground to obtain a paste; Adding a polyvinyl alcohol resin aqueous solution to the paste, mixing evenly, and curing to obtain the polymer-based composite material thermal interface material; The cyclopentadienylruthenium gas is introduced at 330°C and 10 -5 Under the pressure of Pa, cyclopentadienylruthenium gas is introduced, and the cyclopentadienylruthenium gas stays in the cavity for more than 1 s; The steps of preparing the carbon nanotube three-dimensional network structure include: dispersing carbon nanotubes and a surfactant in a solvent to prepare a carbon nanotube dispersion with a concentration of 5wt%; coating the carbon nanotubes in the carbon nanotube dispersion on a silicon substrate, drying and removing the solvent to obtain a carbon nanotube film structure; subjecting the carbon nanotube film structure to a heat treatment to obtain the carbon nanotube three-dimensional network structure; the mass ratio of the carbon nanotubes to the surfactant is 5-10:1; the solvent is water or an organic solvent; the surfactant is sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, polyvinyl pyrrolidone or sodium deoxycholate; the heating treatment is: heating at 300-400°C in air for 1-3 hours, and then heating at 600-1000°C for 3-5 hours in an inert atmosphere to remove the surfactant; The particle size of the metal ruthenium-carbon nanotube nano core-shell structure powder is not higher than 10 μm; the metal ruthenium-carbon nanotube ethanol dispersion suspension is prepared by dispersing the metal ruthenium-carbon nanotube nano core-shell structure powder in ethanol at a mass / volume ratio of 1 g:10 mL; When preparing the paste, the mass / volume ratio of the metal ruthenium-carbon nanotube nano core-shell structure powder, the liquid gallium-indium alloy and the metal ruthenium-carbon nanotube ethanol dispersion suspension is 1 g:10 g:10 mL; The mass concentration of the polyvinyl alcohol resin aqueous solution is 10%; The mass / volume ratio of the liquid gallium-indium alloy and the polyvinyl alcohol aqueous solution in the paste is 10 g:20 mL.

2. The preparation method according to claim 1, characterized in that: The curing temperature is 45 to 55° C. and the curing time is 2 to 5 hours.

3. A polymer-based composite thermal interface material prepared by the preparation method as claimed in claim 1 or 2.

4. An application of the polymer-based composite thermal interface material as claimed in claim 3 in improving the stability of electronic device systems.

Citation Information

Patent Citations

  • Thermally conductive composition and method for preparing the same

    CN101035876A

  • Large scale manufacturing of nanostructured material

    CN101351594A